2013
DOI: 10.1159/000347196
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic Hormone Profile of Adult Women with Acne

Abstract: Acne in adult women is a hard-to-manage frequent disease with many relapse cases. It mostly interferes with quality of life and causes major social and metabolic losses for patients. This is a transversal retrospective study and the aim was to standardize the research on circulating androgenic hormone levels and to detect hyperandrogenic states early, showing the frequency and the pattern of the altered hormones, useful resources to correctly evaluate each patient. In this study 835 women above 15 years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 31 publications
3
30
0
14
Order By: Relevance
“…3 In a study done in Brazil 54.56% of patients with acne vulgaris had hyper androgenism but the most frequently elevated hormone was dehydroepiandrosterone, however only testosterone is measured in this study and it is a case controlled while the Brazilian study was retrospective and included 835 women. 8 The severity of acne has also been linked with hyperandrogenism in a study conducted by Alan et al in Antalya that included 145 patients and 73 healthy subjects and they concluded higher prevalence of hyperandrogenism and obesity among patients with acne vulgaris. 9 Not only high serum levels of testosterone has been documented in patients with acne vulgaris, but low estrogen level is also found according to a an article by Arora MK et al from New Delhi, who screened more than 1000 studies and concluded that various endogenous hormones play important role in the pathogenesis of acne vulgarism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In a study done in Brazil 54.56% of patients with acne vulgaris had hyper androgenism but the most frequently elevated hormone was dehydroepiandrosterone, however only testosterone is measured in this study and it is a case controlled while the Brazilian study was retrospective and included 835 women. 8 The severity of acne has also been linked with hyperandrogenism in a study conducted by Alan et al in Antalya that included 145 patients and 73 healthy subjects and they concluded higher prevalence of hyperandrogenism and obesity among patients with acne vulgaris. 9 Not only high serum levels of testosterone has been documented in patients with acne vulgaris, but low estrogen level is also found according to a an article by Arora MK et al from New Delhi, who screened more than 1000 studies and concluded that various endogenous hormones play important role in the pathogenesis of acne vulgarism.…”
Section: Resultsmentioning
confidence: 99%
“…Facial examination was done according to The American Academy of dermatology classification scheme for acne. 8 General…”
Section: Methodsmentioning
confidence: 99%
“…Şiddetli, ani ve geç başlangıçlı, tedaviye dirençli aknesi olan kadınlarda, özellikle hirsutizm, düzensiz menstrüasyon veya infertilitenin eşlik ettiği durumlarda PKOS'u kapsayan hiperandrojenemi araştırılmalıdır 6 . Hiperandrojenemi en sık karşılaşılan endokrin hastalıklardan bir tanesidir ve üreme çağındaki kadınların %5-10'unu etkiler 19 . Androjenler pilosebase ünitenin fizyolojik gelişimi için gerekli hormonlardır.…”
Section: Bulgularunclassified
“…Androjen fazlalığı kadınlarda saçlı deride alopesi gelişimi, kilo artışı ve obeziteye neden olabilir 20 . Hiperandrojenemisi olanlarda kan dolaşımında yüksek toplam kolesterol ve LDL kolesterol düzeyi, artmış insülin direnci, yüksek tip 2 diabetes mellitus ve kardiyovasküler hastalık gelişme riski mevcuttur [19][20][21] . Sekonder akne nedenlerinden PKOS, ovarian tümör, adrenal tümör ilişkili virilizm hariç tutulursa, idiyopatik aknede hormonal düzey anormalliklerine nadiren rastlanır.…”
Section: Bulgularunclassified
See 1 more Smart Citation